Prevalence and risk factors of Low Birth Weight in Fars province, south of Iran, 2014 - Alireza Mirahmadizadeh; Ali Soleimani; Fariba Moradi; Elham Hesami; Maryam Kasraeian; Hamed Delam (Journal of Health Sciences and Surveillance System, 2017)
Background/Objective: This study was conducted to assess the prevalence of low birth weight and its risk factors in Fars province, south of Iran, 2014.